Kontribusi Remunerasi, Lingkungan Kerja dan Kompetensi terhadap Kinerja Pegawai pada Fakultas Kedokteran Universitas Pendidikan Ganesha - I.K. Sumardana; I.G.K.A. Sunu; I.N. Natajaya (Pascasarjana Universitas Pendidikan Ganesha, 2022)
This study aims to determine the magnitude of the effect of remuneration, work environment, and competence on employee performance in the Faculty of Medicine, Ganesha University of Education. This study uses an